Henry & Eva and the castle on the cliff - Portes, Andrea (Harper, an imprint of HarperCollins Publishers, 2018)
Henry's and Eva's lives are forever changed when their parents die in a mysterious boating accident. That was a very bad day, but things are going to get worse. Their uncle Claude the Clod and his awful girlfriend, Terri the Terrible, have moved into the children's house on the cliff "to take care of them," but Eva has her doubts about their intentions. And when some spooky visitors appear with a message, Henry and Eva realize that their parents' deaths might not have been as cut-and-dried as everyone thinks. Can this brother and sister team (and their group of ghastly, ghostly graveyard friends) uncover the truth before it's too late?--